Perbedaan Hasil Belajar Ilmu Pengetahuan Alam (IPA) dengan Menggunakan Model Pembelajaran Think Talk Write (TTW) dan Think Pair Share (TPS) - Annisa Restu Wardhany; Gufron Amirullah (Jurnal Inovasi Pendidikan Dasar, 2017)
The aim of this research is to determine the difference of science learning outcome between the application of Think Talk Write and Think Pair Share learning models. The research method was a quasi-experimental. The sample of this research were 34 students for first experiment group (VA) and 28 students for second experiment group (VB). Sampling technique was a saturated sampling. The data was collected using multiple choice test that was consist of 30 questions with four choice for the answer. The normality of posttest data was analyzed by using Liliefors test which obtained that both of two experiment groups were normal distributed and the homogeneity of posttest data was analyzed by using Fisher test which obtained that both of them had a similar variance. Based on t-test result, tobs was obtained 3.46 and ttable was obtained 2.00 with df = 60 and alpha = 0.05, therefore, H0 was rejected. The result of this research can be concluded that there was a significant difference of science learning outcome between the application of Think Talk Write and Think Pair Share learning models.